Current technology for the industrial manufacture of snake antivenoms. (1st September 2018) - León, Guillermo; Vargas, Mariángela; Segura, Álvaro; Herrera, María; Villalta, Mauren; Sánchez, Andrés; Solano, Gabriela; Gómez, Aarón; Sánchez, Melvin; Estrada, Ricardo; Gutiérrez, José María
Abstract: Snake antivenoms are formulations of animal immunoglobulins used in the treatment of snakebite envenomation. The general scheme for producing snake antivenoms has undergone few changes since its development more than a century ago; however, technological innovations have been introduced in the manufacturing process. These medicines must comply with identity, purity, safety and efficacy profiles, as requested by the current Good Manufacturing Practices (GMPs) applied to modern biopharmaceutical drugs. Industrial production of snake antivenoms comprises several stages, such as: 1) production of reference venom pools, 2) production of hyperimmune plasma, 3) purification of the antivenom immunoglobulins, 4) formulation of the antivenom, 5) stabilization of the formulation, and 6) quality control of in-process and final products. In this work, a general review of the existing technology used for the industrial manufacture of snake antivenoms is presented. Highlights: Snakebite envenomation is an important public health problem around the world. Antivenoms are the only effective therapy to control snakebite envenomations. Antivenoms must comply with identity, purity, safety and efficacy profiles, according to GMPs. Antivenom manufacture involves several stages. A review of the technology used for the manufacture of snake antivenoms is presented.